AGE-RELATED MORPHOLOGICAL CHANGES IN ALCOHOLIC LIVER CIRRHOSIS: A PATHOMORPHOLOGICAL AND HISTOLOGICAL ANALYSIS IN UZBEKISTAN, 2020–2025 - Koshimuratova , Manzura (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Alcoholic liver cirrhosis (ALC) causes 1.48 million deaths yearly, with rising prevalence in younger groups (25–34 years) and age-specific morphological patterns. This study examines age-related pathomorphological and histological changes in ALC among Uzbeks from 2020–2025, focusing on steatosis, fibrosis, and hepatocellular carcinoma (HCC). Analyzing 150 biopsy/autopsy specimens with H&E, Masson’s trichrome, and METAVIR scoring, results show younger patients (25–34) with 80% microvesicular steatosis and rapid F3–F4 fibrosis (2–3 years), while older (50+) exhibit 65% nodular regeneration and 15% HCC. Statistical tests (Chi-square, ANOVA) confirm significant differences in fibrosis (p<0.01) and necroinflammation (p<0.05). Findings support age-tailored diagnostics and prevention, amid Uzbekistan's rising alcohol use (8.1 liters/capita by 2025), offering insights for resource-limited settings.